Object-oriented Oracle - Rahayu, Johanna Wenny; Taniar, David; Pardede, Eric, 1975- (Hershey, PA : CyberTech Pub., 2005)
"The book covers comprehensive and fundamental aspects of the implementation of object-oriented modeling in a DBMS that was originated as a pure Relational Database, Oracle"--Provided by publisher.
Περιέχει βιβλιογραφία και ευρετήριο
Keywords: Oracle (Computer file); Object-oriented methods (Computer science).